1998
DOI: 10.1046/j.1365-2141.1998.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 12 is seen within a specific subtype of B‐cell chronic lymphoproliferative disease affecting the peripheral blood/bone marrow and co‐segregates with elevated expression of CD11a

Abstract: In order to delineate the specific morphological and immunophenotypic features of B-cell lymphoproliferative disorders associated with trisomy 12, 172 sequential unselected cases of CD19 + CD5 + B-cell disorders, primarily affecting the peripheral blood and bone marrow, were studied. Trisomy 12 was found in 24 cases (13.9%), with all cases morphologically classified as either CLL-PL or CLLmixed by FAB criteria. Trisomy 12 was not found in any cases of typical CLL. Trisomy 12 cases demonstrated a significant hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…This finding was somewhat unexpected in light of several studies that have shown an apparent correlation between morphology and immunophenotype (65)(66)(67)(68)(69)(70)(71). In addition, CLL with trisomy 12 has been associated with atypical morphology (65)(66)(67)(68)(69)(70)(71).…”
Section: Comparison Of Cases With Two Samples From the Same Patientmentioning
confidence: 80%
See 2 more Smart Citations
“…This finding was somewhat unexpected in light of several studies that have shown an apparent correlation between morphology and immunophenotype (65)(66)(67)(68)(69)(70)(71). In addition, CLL with trisomy 12 has been associated with atypical morphology (65)(66)(67)(68)(69)(70)(71).…”
Section: Comparison Of Cases With Two Samples From the Same Patientmentioning
confidence: 80%
“…This finding was somewhat unexpected in light of several studies that have shown an apparent correlation between morphology and immunophenotype (65)(66)(67)(68)(69)(70)(71). In addition, CLL with trisomy 12 has been associated with atypical morphology (65)(66)(67)(68)(69)(70)(71). Furthermore, cases of CLL with trisomy 12 have been shown to be associated with an atypical immunophenotype including increased CD20 expression (66,70) and expression of FMC7 (65,68,70,71).…”
Section: Comparison Of Cases With Two Samples From the Same Patientmentioning
confidence: 86%
See 1 more Smart Citation
“…5,15 The implications of this observation were investigated in a large cohort of patients with trisomy 12 detectable by fluorescence in-situ hybridization. In agreement with previous reports, CLL cases with trisomy 12 had significantly higher expression of CD38 compared with CLL cells from the other major cytogenetic categories (P , .0001) ( Figure 5A).…”
Section: Impact Of Notch1 Mutations On Integrin Expression In Trisomymentioning
confidence: 99%
“…4 The increased prevalence of trisomy 12 in these lymphomas is of particular interest in light of studies reporting increased expression of the a-integrins CD11a and CD49d on trisomy 12 CLL cells. 5,6 The heterodimeric integrins CD11a/CD18 (LFA-1), CD11b/CD18 (Mac-1), CD49d/CD29 (very late antigen-4 [VLA-4]), and CD49d/ITGB7 are cell surface transmembrane proteins involved in the inducible adhesion of leukocytes to vascular walls during the process of transendothelial migration from the bloodstream into the tissues. This process is particularly important in CLL as it allows the malignant cells to enter lymphoid organs where they receive growth and survival signals and are protected from chemotherapy by a network of interactions with the lymph node (LN) microenvironment.…”
Section: Introductionmentioning
confidence: 99%